2017
DOI: 10.3390/nu9040414
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Apoptosis of Chondrocytes through Activation ERK1/2 Signaling Pathways Induced Autophagy

Abstract: Osteoarthritis (OA) is an inflammatory disease of load-bearing synovial joints that is currently treated with drugs that exhibit numerous side effects and are only temporarily effective in treating pain, the main symptom of the disease. Consequently, there is an acute need for novel, safe, and more effective chemotherapeutic agents for the treatment of osteoarthritis and related arthritic diseases. Curcumin, the principal curcuminoid and the most active component in turmeric, is a biologically active phytochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 35 publications
5
70
2
1
Order By: Relevance
“…Shi et al showed that autophagy levels were signi cantly inhibited after activation of the p38 signaling pathway in osteoarthritis [40]. In addition, Li X et al reported that the ERK1/2 signaling pathways activation was involved in chondrocyte autophagy, which protected chondrocyte from apoptosis [41]. Moreover, Pathways such as AMPK/mTOR [42], PI3K/AKT [43], and AKT/mTOR [39] were associated with autophagy in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al showed that autophagy levels were signi cantly inhibited after activation of the p38 signaling pathway in osteoarthritis [40]. In addition, Li X et al reported that the ERK1/2 signaling pathways activation was involved in chondrocyte autophagy, which protected chondrocyte from apoptosis [41]. Moreover, Pathways such as AMPK/mTOR [42], PI3K/AKT [43], and AKT/mTOR [39] were associated with autophagy in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its inherent anti-inflammatory, antioxidative stress, and anticatabolic properties, CUR can mitigate the pathogenesis and symptoms of various diseases, including osteoarthritis [20], Alzheimer's disease [21], and atherosclerosis [22]. Moreover, CUR has been recently demonstrated to induce autophagy in diverse tissues, such as cartilage [23], heart [24], and liver [25], but whether the NP is included among such tissues remains unknown. Given the established link between autophagy and oxidative stress and the ability of CUR to promote autophagy, an enhanced understanding of how CUR affects the NP might facilitate the development of clinically safe, orally available therapeutic agents for IDD.…”
Section: Introductionmentioning
confidence: 99%
“…Treating OA is associated with high costs, 8 and its occurrence and progression are associated with various risk factors, such as aging, genetics, obesity, overuse, infection, and joint injury. 9,10 Cartilage is well known as an avascular connective tissue in which the sole cell type, the chondrocyte, obtains nutrition, and oxygen via diffusion from synovial fluid and subchondral bone. [11][12][13] Substantial evidence has revealed that chondrocyte apoptosis, chondrocyte phenotype loss, and synovial inflammation, which are characterized by the overproduction of pro-inflammatory mediators (including tumor necrosis factor-α (TNF-α) and interleukin (IL)-1β) play a vital role in the occurrence and progression of OA, particularly in the early stages.…”
Section: Introductionmentioning
confidence: 99%